Job Analysis With Comparation Table Methode of Questionaire, Interview and Observation - Suhada, Ahmad Adityareza Taruna; Ghazali, Achmad (Journal of Business and Management, 2015)
Abstract- The main theme of this study is the Human Resource Management and focus on doing the job analysis. The sub - focus of this study is in the job description of an employee in order to achieve the goals and vision of the company. The purpose of this study is to create jobs? according to the distribution of positions within the company and the vision of the PT. ECU. The author uses three approaches to obtain data needed like: using questionnaires, interviews, and observations. The data from job analysis then the author elaborate to create a job description and job specification. Implementation of this research will help employees to work more efficiently and assist in the recruitment of new employees in accordance with company requirements.Â Keyword: Human Resource Management, Job Analysis, Job Description, Job Specification